Sonophotocatalytic degradation mechanisms of Rhodamine B dye via radicals generation by micro- and nano-particles of ZnO - Lops, Carmine (Appl Catal B, 2019)
In this work, it is proposed an environmental friendly sonophotocatalytic approach to efficiently treat polluted waters from industrial dyes exploiting ZnO micro- and nano-materials. For the first time, we deeply investigated the generation of reactive oxygen species (ROS) under ultrasound stimulation of different ZnO structures by Electron Paramagnetic Resonance Spectroscopy (EPR). Indeed, five zinc oxide (ZnO) micro- and nano-structures, i.e. Desert Roses (DRs), Multipods (MPs), Microwires (MWs), Nanoparticles (NPs) and Nanowires (NWs), were studied for the Rhodamine B (RhB) sonodegradation under ultrasonic irradiation. The DRs microparticles demonstrated the best sonocatalytic performance (100% degradation of RhB in 180 min) and the highest OH(·) radicals generation under ultrasonic irradiation. Strikingly, the coupling of ultrasound and sun-light irradiation in a sonophotodegradation approach led to 100% degradation efficiency, i.e. color reduction, of RhB in just 10 min, revealing a great positive synergy between the photocatalytic and sonocatalytic mechanisms. The RhB sonophotocatalytic degradation was also evaluated at different initial dye concentrations and with the presence of anions in solution. It was demonstrated a good stability over repeated cycles of dye treatment, which probe the applicability of this technique with industrial effluents. In conclusion, sonophotocatalytic degradation synergizing sunlight and ultrasound in the presence of DRs microparticles shows a great potential and a starting point to investigate further the efficient treatment of organic dyes in wastewater.